Anxiety and depression symptoms mediate the impact of neuroticism on insomnia in adults with epilepsy: a cross-sectional study - Pan Hu; Kairui Li; Yu Han; Xuefeng Wang; Zheng Xiao (BMC Neurology)
Abstract Objective Comorbid insomnia is a common global occurrence among patients with epilepsy (PWE). Neuroticism could be a significant underlying factor for insomnia in this population. This study aimed to explore whether and how neuroticism, anxiety, and depressive symptoms interact and impact insomnia in PWE. Methods We recruited a continuous cohort of adult PWE. Demographic, clinical data, and information on neuroticism, anxiety, depression, and insomnia were collected. Assessments were conducted using the Eysenck Personality Questionnaire-Revised, Short Scale for Chinese (EPQ-RSC), Generalized Anxiety Disorder-7 (GAD-7), Neurological Disorders Depression Inventory for Epilepsy (NDDI-E), and Insomnia Severity Index (ISI). Process mediation analysis were employed to Investigate the relationships between neuroticism, anxiety, depression, and insomnia. Significant mediation effects were determined using the Bootstrap method with the SPSS PROCESS macro. Results We enrolled a total of 231 adult epilepsy patients in our study. Neuroticism demonstrated a significant positive association with symptoms of anxiety, depression, and insomnia. Neuroticism significantly predicted insomnia in patients. Anxiety symptoms and depressive symptoms exhibited multiple mediating effects between neuroticism and insomnia. Specifically, the direct effect of neuroticism on insomnia accounted for 40.20% of the total effect, while the indirect effects through anxiety symptoms and depressive symptoms, respectively, accounted for 31.52% and 28.28% of the total effect of neuroticism on insomnia. Conclusions Neuroticism, anxiety, and depressive symptoms are interrelated and associated with insomnia in patients with epilepsy. Partially mitigating the negative impact of neuroticism on insomnia by reducing the occurrence of anxiety and depressive symptoms may help reduce the risk of insomnia in PWE.